Discovery of anti-SARS-CoV-2 secondary metabolites from the heartwood of Pterocarpus santalinus using multi-informative molecular networking - Wasilewicz, Andreas; Zwirchmayr, Julia; Kirchweger, Benjamin; Bojkova, Denisa; Cinatl, Jindrich; Rabenau, Holger F.; Rollinger, Judith M.; Beniddir, Mehdi A.; Grienke, Ulrike (Frontiers in Molecular Biosciences, 2023)
A pigment-depleted extract from the heartwood of Pterocarpus santalinus L. f. (PS-DE) showed promising anti-SARS-CoV-2 activity with an IC50 of 29.9 μg/mL in Caco-2-F03 cells. To determine the potential active constituents within the extract prior to isolation, multi-informative molecular network (MN) was applied. Therefore, the extract was separated by high-performance counter-current chromatography (HPCCC) into 11 fractions which were subsequently tested for anti-SARS-CoV-2 activity and analysed by UPLC-tandem mass spectrometry (MS2). The resulting MN combines the bioactivity data of the fractions with the MS2 data. The MN analysis led to the targeted isolation of seven compounds including one pterocarpan (7) reported for the first time as constituent of P. santalinus and four so far undescribed natural products (NPs) that belong to the compound classes of arylpropanes (9), isoflavanones (10) coumestans (16) and 3-arylcoumarins (17), respectively. In total, 15 constituents from the heartwood of P. santalinus and one synthetic isoflavonoid that is structurally related to the natural metabolites were tested for anti-SARS-CoV-2 activity. Thereby, the two pterocarpans (−)-homopterocarpin (5) and (−)-medicarpin (2), the stilbene (E)-pterostilbene (1) and the isoflavonoid 7-O-methylgenistein (11) showed a distinct antiviral activity with IC50 values of 17.2, 33.4, 34.7, and 37.9 µM, respectively, and no cytotoxic effects against Caco-2-F03 cells (CC50 > 100 µM). In addition, a structure-activity relationship (SAR) was proposed indicating structural requirements of pterocarpans for anti-SARS-CoV-2 activity. The herein presented results support the implementation of multi-informative molecular networks as powerful tool for dereplication and targeted isolation of bioactive NPs.